Media Pengenalan Aksara Bali untuk Sekolah Dasar Kelas Rendah Berbasis Motion graphic - I Kadek Rus Sukadana; Sarjono Sarjono; Saiful Yahya (LPPM STIKI Malang, 2021)
Balinese script has become a local content subject starting from elementary school to secondary education level, but Balinese script which still uses learning methods from book media is one factor in the disinterest in learning Balinese script, resulting in reduced children's interest in learning Balinese script. a new media to increase children's interest in learning Balinese script, namely the introduction of Balinese script for low-grade elementary schools based on motion graphics. The design of the Balinese script recognition media uses data collection methods such as observations, interviews, and documents. For the design method using pre-production, production and post-production stages. The final result of the introduction of Balinese script for elementary schools based on motion graphics produces Balinese script recognition media in the form of motion graphics as the main media as well as supporting media in the form of posters, X-banners and Instagram feet and merchandise. Conclusion The design of Balinese script recognition media for low grade elementary schools based on motion graphics has been successfully designed as a Balinese script recognition media using motion graphics.